Urgency of Medical Justice Post Law Number 17 of 2023 Concerning Health - Milenia Ramadhani (PT FORMOSA CENDEKIA GLOBAL, 2024)
Medical dispute resolution in Indonesia has become an important topic along with the increasing number of cases of medical malpractice and negligence. The recently passed Law Number 17 of 2023 concerning Health provides a new direction in regulating medical disputes, emphasizing non-litigation resolution through mediation, arbitration, and a restorative justice approach. However, although this law offers better protection for medical personnel and patients, the urgency of establishing a medical court remains necessary. This is because the existing medical dispute resolution procedures often do not create a sense of justice for both parties, both medical personnel and patients. A medical court that has a specialty is expected to ensure justice by involving judges and experts who understand complex medical issues. Thus, medical courts have the potential to become institutions that accommodate the need for fast, fair, and appropriate resolution of medical disputes in accordance with legal standards and medical professional ethics. This study aims to describe the resolution of medical disputes after the enactment of Law Number 17 of 2023 and analyze the urgency of establishing a medical court to improve the quality of the health law system in Indonesia.